Molecular and clinicopathological characteristics of ROS1‐rearranged non‐small‐cell lung cancers identified by next‐generation sequencing. Issue 11 (14th September 2020) - Cui, Meiying; Han, Yuchen; Li, Pan; Zhang, Jianying; Ou, Qiuxiang; Tong, Xiaoling; Zhao, Ruiying; Dong, Nan; Wu, Xue; Li, Wencai; Jiang, Guozhong
Abstract : ROS1 gene rearrangements have been reported in diverse cancer types including non‐small‐cell lung cancer (NSCLC), and with a notably higher prevalence in lung adenocarcinoma. The tyrosine kinase inhibitors, crizotinib, lorlatinib, and entrectinib, have demonstrated favorable efficacy in treating ROS1‐ rearranged NSCLCs. Herein, we retrospectively reviewed 17 158 NSCLC patients whose tumor specimen and/or circulating cell‐free DNA underwent comprehensive genomic profiling. A total of 258 unique patients were identified with ROS1 rearrangements, representing an overall prevalence of approximately 1.5% of ROS1 fusions in newly diagnosed and relapsed NSCLC patients. CD74 (38%) was the most common fusion partner of ROS1, followed by EZR (13%), SDC4 (13%), SLC34A2 (10%), and other recurrent fusion partners with lower frequencies, including TPM3, MYH9, and CCDC6 . Variant breakpoints occurred in ROS1 introns 33 (37%), 31 (25%), 32 (17%), and 34 (11%) with no obvious hotspots. CD74 (63%) and EZR (50%) were more frequently fused to ROS1 intron 33 than other introns, while ROS1 intron 31 was most frequently fused with SDC4 (79%) and SLC34A2 (81%). Crizotinib progression‐free survival (PFS) was not significantly different between fusion variants involving breakpoints in different ROS1 introns, nor was there a significant difference in PFS between CD74‐ROS1 and non‐ CD74 ‐ ROS1 groups of patients. Furthermore, TP53 was most frequently mutated in patients who progressed on crizotinib, and TP53 mutations were significantly associated with shorter crizotinib PFS. ROS1 mutations, including G2032R, were observed in approximately 33% of post‐crizotinib samples. Collectively, we report the prevalence of ROS1 fusions in a large‐scale NSCLC population and the efficacy of crizotinib in treating patients with ROS1‐ rearranged NSCLC. Abstract : Using next‐generation sequencing, this study found that the prevalence of ROS1 fusions in a large cohort of non‐small‐cell lung cancers (NSCLCs) was 1.5%, including most frequent fusion partners and rare ROS1 fusion pairs. Crizotinib demonstrated robust response in treating patients with ROS1 ‐rearranged NSCLC. TP53 mutations in ROS1 ‐positive patients were significantly associated with shorter crizotinib progression‐free survival.